GAMBARAN MINAT BELAJAR DAN HASIL BELAJAR MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - MUHAMMAD HELMI AZAZI; IKHFANA SYAFINA (LP2MTBM MAKARIOZ, 2023)
Interest is the tendency of people to be interested in an experience and to continue to do so. This tendency persists even when a person is busy doing other things. Activities that are followed by someone because the activity is interesting to him which is the embodiment of his interest, then there is a change in behavior. Student learning outcomes are everything that students get after experiencing the learning process. Everything that is intended, such as changes in behavior, understanding, skills, attitudes, and so on are relatively permanent in students. This research is aimed at the research block. Research block is a block where students will be prepared for their research skills. This block consists of five main topics such as research methodology, statistics, evidence-based medicine, ethics and Islamic perspectives on research. the purpose of this study was to describe the interest in learning and student learning outcomes of the Faculty of Medicine, University of Muhammadiyah North Sumatra. This study is a descriptive study with a cross-sectional research design. The sample in this study amounted to 177 people. The highest student interest was low interest, namely 166 people (93.8%). Meanwhile, student learning outcomes as indicated by the block test scores, most students got B grades as many as 128 people (72.3%). Most of the students have low interest in learning, even though their scores are good. Therefore, students must improve themselves so that they always have a high interest in learning so that they can get good learning outcomes.